2022
DOI: 10.1556/2006.2022.00027
|View full text |Cite
|
Sign up to set email alerts
|

What the grey literature can contribute to addictive behaviour disorder classification •

Abstract: This commentary examines the proposal made by Brand et al. (2022) regarding a framework outlining relevant criteria for considering possible behavioural addictions within the current World Health Organisation's International Classification of Diseases (ICD-11) category of ‘other specified disorders due to addictive behaviours’. We agree with the framework as it highlights the clinical perspective requiring agreed-upon classifications and criteria to produce effective diagnostic procedures and efficacious treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The third debate paper also concentrates on CSBD and concluded that there is currently not enough empirical support for considering CSBD a behavioral addiction ( Sassover & Weinstein, 2022 ). Of the eleven commentaries, seven relate to CSBD ( Borgogna & Aita, 2022 ; Briken & Turner, 2022 ; Bőthe, Koós, & Demetrovics, 2022 ; Castro-Calvo et al., 2022 ; Jennings, Gleason, & Kraus, 2022 ; Lew-Starowicz & Coleman, 2022 ; Rumpf & Montag, 2022 ) and four to the meta-level criteria ( Griffiths, 2022 ; Gullo, Wood, & Saunders, 2022 ; Kuss & Lopez-Fernandez, 2022 ; Stein & Lochner, 2022 ), although there are also commentaries which included both a discussion of the meta-criteria and related topics and a discussion of specific criteria for CSBD (e.g., Borgogna & Aita, 2022 ; Griffiths, 2022 ; Jennings et al., 2022 ; Rumpf & Montag, 2022 ). This overlap is not surprising given that CSBD (or problematic pornography use or “pornography-use disorder” more specifically) is one example of a potential disorder to be considered as “other specified disorders due to addictive behaviors” in the debate paper on meta-criteria ( Brand et al., 2022 ).…”
mentioning
confidence: 99%
“…The third debate paper also concentrates on CSBD and concluded that there is currently not enough empirical support for considering CSBD a behavioral addiction ( Sassover & Weinstein, 2022 ). Of the eleven commentaries, seven relate to CSBD ( Borgogna & Aita, 2022 ; Briken & Turner, 2022 ; Bőthe, Koós, & Demetrovics, 2022 ; Castro-Calvo et al., 2022 ; Jennings, Gleason, & Kraus, 2022 ; Lew-Starowicz & Coleman, 2022 ; Rumpf & Montag, 2022 ) and four to the meta-level criteria ( Griffiths, 2022 ; Gullo, Wood, & Saunders, 2022 ; Kuss & Lopez-Fernandez, 2022 ; Stein & Lochner, 2022 ), although there are also commentaries which included both a discussion of the meta-criteria and related topics and a discussion of specific criteria for CSBD (e.g., Borgogna & Aita, 2022 ; Griffiths, 2022 ; Jennings et al., 2022 ; Rumpf & Montag, 2022 ). This overlap is not surprising given that CSBD (or problematic pornography use or “pornography-use disorder” more specifically) is one example of a potential disorder to be considered as “other specified disorders due to addictive behaviors” in the debate paper on meta-criteria ( Brand et al., 2022 ).…”
mentioning
confidence: 99%